Review on infectious diseases - N, Susmitha; P, Narayana Swamy; P, Venkatesh (International Journal of Indigenous Herbs and Drugs, 2022)
An infectious disease is caused by a parasite (Virus, Bacteria, and Protozoa etc.). The infecting organism or pathogen interferes with the normal functioning of the host and can lead to chronic wounds, gangrene and even death. So, providing knowledge regarding the common infectious diseases is very much essential criteria to the common peoples. The study method was proceeded to assess the knowledge, attitudes and practices of the patient regarding the infectious diseases by the self administered knowledge, attitudes and practices (KAP) questionnaire (base line readings) and then included the handover of pre evaluated patient information leaflet as a counseling aid to the study participants. Analysed through Paired t test. Follow up study results were found significant (*P<0.05) when compared to baseline results. The scores obtained for self prepared patient information leaflet used is as in between the 60-70. So, the patient information leaflet (PIL) is considered as ‘standard’ as per the Flesch Reading Ease Formula. Among all Flesch Reading Ease values patient information leaflet for Dengue fever has shown highest value that is 67.40 and lowest value is obtained for the patient information leaflet of Malaria that is 60.05. Our study concluded that the prepared information leaf let for few infectious diseases prevalence and incidence of anticoagulant induced internal bleeding was high. So, risk management plays important role for the better outcome of the therapy.